THE RELATIONSHIP BETWEEN PATIENTS’ KNOWLEDGE LEVELS AND FAMILY SUPPORT ON DIET COMPLIANCE OF DM PATIENTS IN DR. M.M DUNDA LIMBOTO REGIONAL PUBLIC HOSPITAL - nurananda p sono; rita amini warastuti; astria lolo (Jurnal Ilmiah dr. Aloei Saboe, 2022)
This study aims to determine the relationship between the level of patients’ knowledge and family support on the dietary compliance of DM patients in Dr. M.M Dunda Limboto Regional Public Hospital. The method of the research used was quantitative research. The sampling technique used was an accidental sampling system with total sample of 66 respondents, then analyzed using Chi Square statistical test. The results of the research showed that there was no significant relationship (0,993>0,05) between the patients’ level of knowledge and dietary compliance of DM patients, so Ha1 hypothesis was rejected and H01 hypothesis was accepted, and there was a significant relationship (0,043<0,05) between family support with the dietary compliance of DM patients, then H02 hypothesis was rejected and Ha2 hypothesis was accepted, with the conclusion that the research results showed that there was no relationship between the patients’ level of knowledge on the dietary compliance of DM patients and there was a relationship between family support and dietary compliance of DM patients in Dr. M.M Dunda Limboto Regional Public Hospital.